(untitled) (Boletin Médico de Postgrado, 2020)
Cardiovascular diseases are one of the main causes of mortality worldwide being heart rhythm disorders one of the most frequent cardiac pathologies. Electrical cardioversion is a technique that allows the transfer of electrons to the myocardium in order to interrupt arrhythmias with reentry mechanisms allowing the sinus node to take control of heart rate. The appropriate selection of cases susceptible to electrical cardioversion as well as experience on this technique increases the success rate and decreases the number of failed attempts. The Electrocardiology unit of the CCR-ASCARDIO has experience in the study and treatment of arrhythmias. In this article we present the development of a training program on electrical cardioversion, essential tool for cardiologists, with the aim to increase the correct use of this technique in order to prevent complications due to heart rhythm disorders.